Enhancement of suicide effect of herpes simplex thymidine kinese gene by IL-6 and GM-CSF genes - Mackiewicz, Andrzej; Wiznerowicz, Maciej; Kapcińska, Małgorzata; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 1999)
54 clinical trails of cancer suicide gene therapy comprising 555 patients are currently carried out allover the world. These trails mostly target brain tumors and malignant melanoma, and apply herpes simplex virus type 1 thymidine kinase gene (HSV-1 Tk) as a suicide gene. Following ganciclovir (GCV) administration Tk transduced cancer cells and non-transduced neighboring cancer cells are eliminated ( bystender effect ). Very important role in tumor eradication plays also antitumor immune response. The aim of the study was the enhancement of the suicide gene therapy of melanoma by (i) increase of the bystander effect by IL-6, (ii) combination of suicide gene therapy and immunostimulation using Tk and GM-CSF genes. For this purpose the HyTk fusion gene was inserted into MSCV retroviral vector. Into the same vector bicistronic genes IL-6-IRES-Neo, GM-CSF-IRES-Neo or GM-CSF-IRES-HyTk were cloned. Obtained recombinant retroviruses were used for transduction of B-78-H1 murine melanoma cells. In vitro biological activity of Tk was studied by adding of GCV into culture of B-78-HyTk or B-78-GM-CSF/HyTk. In vivo activity of Tk was studied by s. c. inoculation of C57Bl/6 x C3H mice with 5 x 10 5 B-78-HyTk followed by i.p. GCV (15, 75, 150 mg/kg) administration after 7 days. In another set of experiments mice were inoculated with B-78-HyTk or B-78-IL-6 mixed 1:1 with B-78-H1 cells or B-78-HyTk/B-IL-6 1:1 mixture. After 7 days mice received 75 mg/kg of GCV. In the last series of experiments mice were inoculated s.c. with B-78-H1, B-78-GM-CSF or B-78-GM-CSF/HyTk and after 7 days GCV (75 mg/kg) was applied i.p. We have for the first time demonstrated that IL-6 in the synergistic manner enhanced Tk bystander effect. Moreover, combination of Tk with GM-CSF completely inhibited tumor formation by low-immunogenic murine melanoma B-78-H1, while application of each of the factors separately had only limited effect. We have confirmed earlier observations that bicistronic genes provide high expression of therapeutic gene in retroviral expression system. In addition application of fusion gene (HyTk) allows insertion of two therapeutic genes into cancer cell.